Quercetin and endurance exercise capacity: a systematic review and meta-analysis - Kressler, J.; Millard-Stafford, M.; Warren, G. L. (Medicine & Science in Sports & Exercise, 2011)
Quercetin is a dietary flavonoid purported to improve human endurance exercise capacity. However, published findings are mixed.